A comprehensive review of empirical models for estimating global solar radiation in Africa. (October 2017) - Samuel Chukwujindu, Nwokolo
Abstract: The accurate knowledge of global solar radiation is of vital requirement for surveys in agronomy, hydrology, ecology, sizing of the photovoltaic or thermal solar systems, solar architecture, molten salt power plant and supplying energy to natural processes like photosynthesis and estimates of their performances. However, measurement of global solar radiation is not available in most locations across Africa. During the past 36 years in order to estimate global solar radiation on the horizontal surface on both daily and monthly mean daily basis, numerous empirical models have been developed for several locations in Africa. As a result various input parameters have been utilized and different functional forms used. In this study aim at classifying and reviewing the empirical models employed for estimating global solar radiation in Africa. The empirical models so far utilized were classified into six main categories and presented based on the input parameters employed. The models were further reclassified into several main sub-classes (groups) and finally represented according to their developing year. On the whole, 732 empirical models and 65 functional forms were recorded in literature for estimating global solar radiation in Africa in this review. Thus, this review would provide solar energy researchers in terms of identifying the input parameters and functional forms widely employed up till now as well as recognizing their importance for estimating global solar radiation in several locations in Africa.